Design Thinking Perancangan UI/UX Design Aplikasi Toko kuequ Dengan Metode Pendekatan Design Thinking: UI/UX Design Thinking - Inayah, Euis; Anggraeni Putri , Sukmawati (Jurnal Dinamika Informatika, 2024)
The Covid-19 pandemic was not only hit by the health sector, but many sectors, especially the economic sector, were not only affected, but small industries were also affected, especially MSMEs. For this reason, it is necessary for this application design designer to be able to assist in an easy delivery and payment ordering system. This design uses the design thinking method, which goes through several stages such as Empathy, Define, Ideate, Prototype, & Test. In this design thinking method, interviews, observation,s and usability testing are carried out using Unmoderated Remote Usability, namely conducting remote testing with their respective devices without supervision, opening the prototype link that has been given, and then the researcher asking questions in the form of actually optimising the questionnaire for the test. The design of the application is made to make it easier to solve problems. The design of the kuequ application is integrated into the system. Keywords: UI/UX, Design Thinking, Desain, Low-fidelity, High-fidelity